Associated factors of health-related quality of life among adolescents in Barangays Calit-calit, Muzon, and Libato, San Juan, Batangas - Balmadrid, Ivan Gil.; Blaquera, Allan Paulo; Co, Kim Carmela; Conese, Ana Luisa; Depay, Nikki Mariz; Jbeili, Reginald; Segovia, Marnelle; Tamayo, Jose Victor (Manila College of Nursing, University of the Philippines Manila, 2011)
Adolescents face challenges unique to their developmental stage. Their Health-related
Quality of Life (HRQoL) is affected by factors both from within the individual and his or her
environment. This study aimed to describe the health profile of adolescents in the barangays of Calit-calit, Muzon, and Libato in San Juan, Batangas, ‘n terms of their health-related quality of life. This study is deemed significant as it may serve as basis for policy making and redirection of nursing interventions and programs for adolescent health. Through systematic random sampling, adolescents (n=274) from Barangays Muzon, Calit-calit and Libato in San Juan Batangas, answered KINDL-R and AMA-GAPS tools to evaluate their HRQoL. Results revealed that among the associated factors evaluated, behavior problems yielded the most significant effects, with the addition of sexual practices as the adolescent grows older. There was a significant difference noted between the self-reported HRQoL and the reported HRQoL of parents for their children, which presents a gap in the perceptions of the parent and child. The researchers recommend that the relationship between the associated factors be also evaluated. A larger sample, from diverse backgrounds may also be used to be able to generalize the results for formulation of health policies and programs.
Accomplishment report (In partial fulfillment of the requirements in N121.2: Intensive Community Nursing Experience) -- University of the Philippines Manila, April 2011.
Keywords: Intensive nursing experience